Peran Internal Auditor Untuk Mencegah Terjadinya Fraud Di Dalam Perusahaan - Mei Liana Rofilia Sari; Aginsha Caurel Natasya; Irda Agustin Kustiwi (Jurnal Mutiara Ilmu Akuntansi, 2024)
This article aims to determine the role of internal auditors in preventing conditions or fraud in companies. Acts of circumstances can occur due to opportunity, pressure and rationalization, as mentioned in the fraud triangle. One of the reasons why perpetrators of conditional acts can freely carry out conditional acts is if there is no proper supervision, so that the opportunity to carry out conditional acts comes. Therefore, the role of independent internal auditors in companies is very necessary to suppress opportunities that will be taken by potential perpetrators.